Rapid change of liver stiffness after variceal ligation and TIPS implantation - Piecha, Felix; Paech, Daniel; Sollors, Janina; Seitz, Helmut K.; Rausch, Vanessa; Mueller, Sebastian (American journal of physiology. Gastrointestinal and liver physiology, 2017)
Liver stiffness (LS) as measured by transient elastography is widely used to screen for liver fibrosis. However, LS also increases in response to pressure changes like congestion but no data on portal pressure are available. We study here the effect of rapid portal pressure changes on LS. Therefore, LS was assessed directly prior and after ligation of esophageal varices (n = 11) as well as transjugular intrahepatic portosystemic shunt (TIPS) implantation in patients with established cirrhosis (n = 14). Additionally, we retrospectively analyzed changes in LS and variceal size in patients with sequential gastroscopic monitoring and LS measurements (n = 14). To study LS and portal pressure in healthy livers, LS (µFibroscan; Echosens, Paris, France) and invasive pressures (Powerlab, AD Instruments, New Zealand) were assessed in male Wistar rats after ligation of single liver lobes. Ligation of esophageal varices caused an immediate and significant increase of LS from 40.3 ± 19.0 to 56.1 ± 21.5 kPa. Likewise, LS decreased significantly from 53.1 ± 16.6 to 43.8 ± 17.3 kPa after TIPS placement, which correlated significantly with portal pressure (r = 0.558). In the retrospective cohort, the significant LS decrease from 54.9 ± 23.5 to 47.9 ± 23.8 kPa over a mean observation interval of 4.3 ± 3 mo was significantly correlated with a concomitant increase of variceal size (r = −0.605). In the animal model, LS and portal pressure increased significantly after single lobe ligation without changes of arterial or central venous pressure. In conclusion, rapid changes of portal pressure are a strong modulator of LS in healthy and cirrhotic organs. In patients with stable cirrhosis according to the model for end-stage liver disease (MELD), a decrease of LS may be indicative for enlarging varices.NEW & NOTEWORTHY Liver stiffness (LS) immediately increases after variceal ligation while it decreases after transjugular intrahepatic portosystemic shunt (TIPS) implantation due to portal pressure changes. LS and portal pressure rapidly increase after single lobe ligation in Wistar rats without changes of arterial or central venous pressure. Collateral formation may be one cause for a transient decrease in LS in the absence of other confounders. Such pressure changes should be considered when interpreting LS in clinical practice.